Habitat Selection of Sympatric Lontra felina and L. provocax in Chilean Patagonia: Toward Sustainable Management - Sielfeld, Walter; Bunster, Claudia; Guzman, Jonathan A.; Buscaglia, Marx; Sánchez Jardón, Laura; Clark, Arturo; Briones, Raul (My University, 2025)
Understanding habitat use in sympatric species is key to informing conservation efforts. Lontra felina and L. provocax are semi-aquatic mustelids commonly known as South American marine and southern river otters, respectively, that occupy contrasting coastal environments in southern Chile. We investigated habitat characteristics associated with sightings of both species in the Raúl Marín Balmaceda Multiple Use Protected Area, northern Chilean Patagonia. Our results show L. felina is restricted to exposed, steep rocky shores with sparse vegetation and intertidal belts dominated by Durvillaea antarctica and Lessonia spp., while L. provocax was found to be associated with sheltered, forested margins and estuarine areas dominated by Macrocystis pyrifera and other meadow-forming algae. Records did not show coexistence of both species in the same location; therefore, it is concluded that they exhibit a sympatric but non-syntopic pattern.
Keywords: marine otters; lontra felina; lontra provocax; habitat characterization; northern patagonia